An Olive Oil Mill Wastewater Extract Improves Chemotherapeutic Activity Against Breast Cancer Cells While Protecting From Cardiotoxicity - Benedetto, Nadia; Calabrone, Luana; Gutmańska, Karolina; Macrì, Nicoletta; Cerrito, Maria Grazia; Ricotta, Riccardo; Pelosi, Giuseppe; Bruno, Antonino; Noonan, Douglas M.; Albini, Adriana (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular toxicity in cancer patients receiving chemotherapy remains one of the most undesirable side effects, limiting the choice of the most efficient therapeutic regimen, including combinations of different anticancer agents. Anthracyclines (doxorubicin) and antimetabolites (5-fluorouracil (5-FU), capecitabine) are among the most known agents used in breast cancer and other neoplasms and are associated with cardiotoxic effects. Extra-virgin olive oil (EVOO) is rich in polyphenols endowed with antioxidant cardioprotective activities. Olive mill wastewater (OMWW), a waste product generated by EVOO processing, has been reported to be enriched in polyphenols. In this study, we investigated the activities of polyphenol-rich extract from OMWW, A009, in cooperation with chemotherapy on two breast cancer cell lines, namely, BT459 and MDA-MB-231, in a cardio-oncology perspective. The effects of A009 on cardiac cells were also investigated with and without chemotherapeutic agents. Cell viability was determined on BT459 and MDA-MB-231 (i.e., breast cancer cells) and H9C2 (i.e., rat cardiomyocytes) cells, using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. A spheroids assay was used as a 3D in vitro model on BT459 and MDA-MB-231 cells. For in vivo studies, the murine sponge assay of angiogenesis was used as a model of breast cancer-associated vascularization. The embryo of Danio rerio (zebrafish) was used to detect the cardioprotective activities of the OMWW. We found that the A009 extract exhibited antiangiogenic activities induced by breast cancer cell supernatants and increased T-cell recruitment in vivo. The combination of the OMWW extracts with doxorubicin or 5-FU limited BT459 and MDA-MB-231 cell viability and the diameter of 3D spheroids, while mitigating their toxic effects on the rat H9C2 cardiomyocytes. Cardioprotective effects were observed by the combination of OMWW extracts with doxorubicin in zebrafish embryos. Finally, in human cardio myocytes, we observed 5-FU-induced upregulation of the inflammatory, senescence-associated cytokine IL6 and p16 genes, which expression was reduced by OMWW treatment. Our study demonstrates that the polyphenol-rich purified OMWW extract A009 combined with cancer chemotherapy could represent a potential candidate for cardiovascular protection in breast cancer patients, while increasing the effects of breast cancer chemotherapy.